Impact ionization effect on the generation of nitride-based diodes - Боцула, О. В.; Приходько, К. Г. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 2018)
The operation of AlGaN and InGaN – based diodes in limited space accumulation regime is considered. The generation efficiency to obtain taking impact ionization into account is analyzed. The analysis of the diodes operation was performed using Monte Carlo technique. The impact ionization rate is described in local electric field approximation. The maximal generation efficiencies of diodes under specified frequency and there operation frequency ranges are determined. The energy characteristics have been obtained for different diode’s lengths and material compositions. The Al and In fractions were changed from 0 to 0,4. The impact ionization is showed to effect strongly to operation of InGaN – based diodes and to lead to efficiency decreasing.